Simulation vs workplace-based assessment in resuscitation: a cross-specialty descriptive analysis and comparison - Seed, Jeremy D; Gauthier, Stephen; Zevin, Boris; Hall, Andrew K; Chaplin, Timothy (Canadian Medical Education Journal, 2023)
Background: Simulation-based assessment can complement workplace-based assessment of rare or difficult to assess Entrustable Professional Activities (EPAs). We aimed to compare the use of simulation-based assessment for resuscitation-focused EPAs in three postgraduate medical training programs and describe faculty perceptions of simulation-based assessment. Methods: EPA assessment scores and setting (simulation or workplace) were extracted from 2017-2020 for internal medicine, emergency medicine, and surgical foundations residents at the transition to discipline and foundations of discipline stages. A questionnaire was distributed to clinical competency committee members. Results: Eleven percent of EPA assessments were simulation-based. The proportion of simulation-based assessment did not differ between programs but differed between transition (38%) and foundations (4%) stages within surgical foundations only. Entrustment scores differed between settings in emergency medicine at the transition level only (simulation: 4.82 ± 0.60 workplace: 3.74 ± 0.93). 70% of committee members (n=20) completed the questionnaire. Of those that use simulation-based assessment, 45% interpret them differently than workplace-based assessments. 73% and 100% trust simulation for high-stakes and low-stakes assessment, respectively. Conclusions: The proportion of simulation-based assessment for resuscitation focused EPAs did not differ between three postgraduate medical training programs. Interpretation of simulation-based assessment data between committee members was inconsistent. All respondents trust simulation-based assessment for low-stakes, and the majority for high-stakes assessment. These findings have practical implications for the integration simulation into programs of assessment.